Search for top quark partners with charge 5/3 in the same-sign dilepton and single-lepton final states in proton-proton collisions at √s=13 TeV - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Asilar E. Ece; Bergauer T. Thomas; Babaev A. A. Anton Anatoljevich (2019, 2019)
Title screen